Short-term memory span: Effects of age and relationship with other variables - Bagdonas, A.; Bikulčiūtė, D.; Čepas, V. (Psichologija, 1987)
Jacobs' method was used to study the span of short-term memory (STM), visual (letters, syllables, figures) as well as auditory (numbers), its genetic determination and dependence on age and other variables. An average STM span amounts to 8 figures, 6.6 letters 6.4 syllables, 6.7 elements of all the three types, and 5-6 auditory signal. Preliminary norms for the span of visual STM for students are suggested. At the age from 9 to 25 the increase of the extent of STM is linear. The correlation coefficient of age and the span of auditory STM is 0.47 (for 182 subjects). No differences were observed concerning the span of STM with regard to sex. The twin method did not reveal any effect of genetic factors. The span of STM may change subject to the disturbances of blood circulation in the brains. The span of verbal STM is decreased by the disturbances of blood circulation in the left hemisphere, while the disturbances in the right hemisphere negatively influence the STM for geometrical figures. There is little, if any, correlation between the span of STM and other cognitive functions which have been studied, such as characteristics of memory, reading efficiency, etc. No correlation was established with the span of immediate and delayed reproduction. Notwithstanding the reliability of Jacobs ' method, which was confirmed by repeated studies, its validity might be questioned. Thus the value of the data obtained should be considered critically as there might be certain factors related with mnemic strategies.
Keywords: Short-Term Memory; age